Traffic noise pollution at school in Shah Alam / Adila A/K Abdullah - Abdullah, Adila (Faculty of Architecture, Planning and Surveying, 2013)
Traffic noise pollution around the school area can have a negative impact and affect the performance of both teachers and students. The noise levels should be around 55 dB at the school. Lacks attention is given by individuals and governments relating to noise pollution in the school environment. A study of this problem is carried out by doing some measurement of the noise level at schools located close to the road. This case study was conducted in Sekolah Kebangsaan Bandar Anggerik, Sekolah Kebangsaan Padang Jawa and Sekolah Menengah Kebangsaan Sultan Salahhudin Abdul Aziz Shah. For each school, three days have been allocated for data collection starts from 8.00 am to 8.30 am, 1.30 pm to 2.00 pm and 3.30 pm to 4.00 pm. The noise reading was taken every 5 minutes. The selection of data collection methods is by using a sound level meter and also the distribution of questionnaires to the teachers and staff at each school. The results show that the noise levels in all three schools exceed the standards set by the Malaysian department of environment. The noise level readings are 61.3 dB for Sekolah Kebangsaan Bandar Anggerik, 61.8 dB for Sekolah Menengah Kebangsaan Sultan Salahhudin Abdul Aziz Shah and 63.3 dB for Sekolah Kebangsaan Padang Jawa. The results from this study also found that the level of noise in the Sekolah Kebangsaan Padang Jawa is critical compared to the two schools involved in the study. Some recommendations were suggested to overcome this problem and hopefully it can reduce traffic noise pollution in the school